Università: ricerca e insegnamento - Mario Gennari (Firenze University Press, 2019)
The word universitas evokes the organic unity of sciences, meaning a critical comparison between different scientific paradigms, which are orientied to the civil, economic, social, legal and political development of humanity. The institutional activities of University are focused therefore on study and research, which precede teaching and learning. However, the cultural and scientific policies are countered by logic of corruption, careerism, the fragmentation of knowledge and a bureaucratic substratum, which risks losing the purpose of the university institution.